High levels of genetic recombination among cotransfected plasmid DNAs in poxvirus-infected mammalian cells. - Evans, D H (1988)
The frequency of recombination between transfected plasmid DNAs was measured by using cultured cells infected with a variety of poxviruses. Plasmid derivatives of pBR322 containing XhoI linker insertion mutations in the tetracycline gene were used to assess recombination frequencies in rabbit cells infected with the leporipoxviruses Shope fibroma virus and myxoma virus and the orthopoxvirus vaccinia virus. Recombination frequencies were calculated by Southern blotting, which detects novel plasmid restriction fragments generated by genetic recombination, and by a plasmid rescue procedure in which the reconstruction of an intact tetracycline gene in the transfected rabbit cell was monitored by transformation back into Escherichia coli. The highest recombination frequencies were measured in cells infected with Shope fibroma virus and myxoma virus, and a minimum recombination frequency of at least one recombination event per 7 kilobases was calculated within 24 h posttransfection under these conditions. The deduced recombination frequency in vaccinia virus-infected cells was at least fivefold lower and was not detectable in mock-infected cells, suggesting that the induced recombination activity detected by these methods was under viral control. The results of kinetic studies, analysis with methylation-sensitive restriction enzymes, and the use of phosphonoacetic acid, a specific inhibitor of poxvirus DNA polymerase, indicated that recombination between transfecting DNAs occurred concomitantly with DNA replication but that the two processes could be partially uncoupled. We conclude that the dramatic expansion of recombination activities in the cytoplasm of poxvirus-infected cells is virus specific and offers a good model system with which to analyze the mechanism of recombination in a eucaryotic environment.